2016
DOI: 10.1016/j.stem.2016.07.002
|View full text |Cite|
|
Sign up to set email alerts
|

An Isogenic Human ESC Platform for Functional Evaluation of Genome-wide-Association-Study-Identified Diabetes Genes and Drug Discovery

Abstract: SUMMARY Genome wide association studies (GWAS) have increased our knowledge of loci associated with a range of human diseases. However, applying such findings to elucidate pathophysiology and promote drug discovery remains challenging. Here, we created isogenic human embryonic stem cells (hESCs) with mutations in GWAS-identified susceptibility genes for type 2 diabetes. In pancreatic betalike cells differentiated from these lines, we found that mutations in CDKAL1, KCNQ1 and KCNJ11 led to impaired glucose secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 32 publications
4
93
0
2
Order By: Relevance
“…21,33 In addition to mouse models, recent studies have generated CDKAL1-deficient β-cells from human embryonic stem cells using CRISPR-Cas9 technology. 41,42 In agreement with mouse studies, C-peptide secretion was also reduced in CDKAL1-deficient β-cells compared to wild-type β-cells.…”
Section: Impaired Insulin Secretionsupporting
confidence: 86%
See 1 more Smart Citation
“…21,33 In addition to mouse models, recent studies have generated CDKAL1-deficient β-cells from human embryonic stem cells using CRISPR-Cas9 technology. 41,42 In agreement with mouse studies, C-peptide secretion was also reduced in CDKAL1-deficient β-cells compared to wild-type β-cells.…”
Section: Impaired Insulin Secretionsupporting
confidence: 86%
“…When Cdkal1‐deficient mice were subjected to a high‐fat diet, these mice exhibited marked impairment of insulin secretion, leading to an acceleration of glucose intolerance and increase of fasting blood glucose (>200 mg/dL) . In addition to mouse models, recent studies have generated CDKAL1‐deficient β‐cells from human embryonic stem cells using CRISPR‐Cas9 technology . In agreement with mouse studies, C‐peptide secretion was also reduced in CDKAL1‐deficient β‐cells compared to wild‐type β‐cells.…”
Section: Phenotypes Of Cdkal1 Knockout Micementioning
confidence: 63%
“…Their β‐cell mass is expanded , and elevated insulin production is sustained for decades, without causing β‐cell “exhaustion.” Accumulating clinical and experimental evidence now supports a primary role of inherited β‐cell abnormalities in T2D pathogenesis. Many of the >100 genetic loci identified in T2D genome‐wide association studies (GWAS) are associated with genes involved in β‐cell function . Recent targeting of three of these candidate genes, CDKAL1 , KCNJ11 , and KCNQ1 (the last two encoding potassium channel proteins), in human pluripotent stem cells, using clustered regularly interspaced short palindromic repeats (CRISPR)‐Cas‐mediated genome editing, was shown to cause defective insulin secretion in β‐like cells differentiated from them .…”
Section: Beta‐cell Failure In Type 2 Diabetesmentioning
confidence: 99%
“…Some are detrimental to β-cell health and could be instrumental in impairing GSIS. For example, genome-wide association studies identified Kcnq1 and Rasgrp1 (RAS guanyl releasing protein 1) as susceptible genes for T2DM (Yasuda et al, 2008; Zeng et al, 2016) and βARKO −/y islets exhibit increased expression of both. Kcnq1 impairs insulin secretion by enhancing the β-cell potassium currents (Yamagata et al, 2011).…”
Section: Discussionmentioning
confidence: 99%